A Chromosome-Level Genome Assembly of Mozambique Tilapia (Oreochromis mossambicus) Reveals the Structure of Sex Determining Regions - Tao, Wenjing; Cao, Jianmeng; Xiao, Hesheng; Zhu, Xi; Dong, Junjian; Kocher, Thomas D.; Lu, Maixin; Wang, Deshou (Frontiers in Genetics, 2021)
The Mozambique tilapia (Oreochromis mossambicus) is a fascinating taxon for evolutionary and ecological research. It is an important food fish and one of the most widely distributed tilapias. Because males grow faster than females, genetically male tilapia are preferred in aquaculture. However, studies of sex determination and sex control in O. mossambicus have been hindered by the limited characterization of the genome. To address this gap, we assembled a high-quality genome of O. mossambicus, using a combination of high coverage of Illumina and Nanopore reads, coupled with Hi-C and RNA-Seq data. Our genome assembly spans 1007 Mb with a scaffold N50 of 11.38 Mb. We successfully anchored and oriented 98.6% of the genome on 22 linkage groups (LGs). Based on re-sequencing data for male and female fishes from three families, O. mossambicus segregates both an XY system on LG14 and a ZW system on LG3. The sex-patterned SNPs shared by two XY families narrowed the sex determining regions to ~3 Mb on LG14. The shared sex-patterned SNPs included two deleterious missense mutations in ahnak and rhbdd1, indicating the possible roles of these two genes in sex determination. This annotated chromosome-level genome assembly and identification of sex determining regions represents a valuable resource to help understand the evolution of genetic sex determination in tilapias.